Analisis Prioritas Belanja Dana Desa Pada Desa Wisata Pulantani Kabupaten Hulu Sungai Utara - Fitri, Maulida; Wardhana, Ali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
Aims of this sudy are first, to discovery of the Process in Village Fund Budgeting Planning in Pulantani Village, Hulu Sungai Utara District second, to find out the appropriate spending priorities for village funds in developing Pulantani village, Hulu Sungai Utara District. The numerous participants in this study were 10 who affect village fund spending in Pulantani village that used Analytical Hierarchy Process method used in data processing. In conclusion, this study signifies the option of criteria for the RPJMDes, Villages’ Potential and issues that affect the determination in that small townspending priorities in the order of selecting village fund spending priorities, namely Village Development 41.60%, followed by Community Empowerment 33.86%, followed by Community Development 16.54%, and the last is Village Administration of 8.62%. With the most dominant conclusion is Village Development 41.60%.